2012
DOI: 10.1111/acv.12012
|View full text |Cite
|
Sign up to set email alerts
|

Use of mineral licks by mammals and birds in hunted and non‐hunted areas of Yasuní National Park, Ecuador

Abstract: Mineral licks are sites where a diverse array of mammals and birds consume soil or drink water, likely for mineral supplementation. Many of those same animals are targets of hunters. Camera traps triggered by heat and motion were used to document use of mineral licks by birds and mammals over approximately 2 months at two lowland forest sites in eastern Ecuador, one that has experienced considerable hunting by indigenous Waorani (four mineral licks) and one that is largely unaffected by hunting (five licks). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 45 publications
3
33
0
4
Order By: Relevance
“…Similarly, the nearest Waorani community is about 30km West of the station and its hunters are occasionally encountered on the Tiputini River near TBS. Yet, an abundance of top predators suggests that prey populations also are abundant, as our previous studies indicated (Blake et al, 2011(Blake et al, , 2012, and would suggest that hunting pressure is relatively slight in the area (Blake et al, 2013). If prey populations were reduced as a consequence of increased hunting activities, however, we could expect to see declines in predator populations as well (Espinosa-Andrade, 2012).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, the nearest Waorani community is about 30km West of the station and its hunters are occasionally encountered on the Tiputini River near TBS. Yet, an abundance of top predators suggests that prey populations also are abundant, as our previous studies indicated (Blake et al, 2011(Blake et al, , 2012, and would suggest that hunting pressure is relatively slight in the area (Blake et al, 2013). If prey populations were reduced as a consequence of increased hunting activities, however, we could expect to see declines in predator populations as well (Espinosa-Andrade, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…Rather, we are evaluating the degree to which multiple individuals overlap in their use of a relatively small area of forest. (Blake, Mosquera, & Salvador, 2013). The closest Kichwa community is ~17km north of the station; jaguars moving in that direction might, on occasion, encounter hunters but are much less likely to do so when moving in any other direction.…”
mentioning
confidence: 99%
“…However, the Matses' failure to distinguish these sympatric cervids in other ecobehavioral respects is hard to reconcile with published evidence that gray brockets are primarily diurnal and do not visit mineral licks, whereas red brockets are often active at night and commonly visit mineral licks (Tobler et al, 2009;Blake et al, 2012Blake et al, , 2013.…”
Section: Mazama Nemorivagamentioning
confidence: 94%
“…Remarks: Matses interviews about red brockets include most of the well-established natural history facts about this widespread species, including its use of floodplain habitats and secondary vegetation (avoided by gray brockets); solitary habits; feline predators; mixed diet of fruit, seeds, and browse; and propensity for visiting mineral licks (e.g., Bodmer, 1989Bodmer, , 1991Gayot et al, 2004;Tobler et al, 2009;Blake et al, 2013). Many other behavioral details, however, are not reported in the literature we consulted, including information about daily movements, geophagy, reptilian predators, and sexual vocalizations.…”
Section: Mazama Americanamentioning
confidence: 99%
See 1 more Smart Citation